2020
DOI: 10.1177/0194599820945953
|View full text |Cite
|
Sign up to set email alerts
|

Time and Cost of Ultrasound‐Guided Fine‐Needle Aspiration Biopsy/Core‐Needle Biopsy for Primary Laryngohypopharyngeal Squamous Cell Carcinoma

Abstract: Objectives This study aimed to evaluate benefits in terms of time and cost of percutaneous ultrasound-guided fine-needle aspiration biopsy/core-needle biopsy (US-FNAB/CNB) for the diagnosis of primary laryngeal and hypopharyngeal squamous cell carcinoma (LHSCC) in comparison with direct laryngoscopic biopsy (DLB) under general anesthesia. Study Design Retrospective case-control study. Setting Single operator of a single center. Subjects and Methods From 2018 to 2019, 28 patients who underwent percutaneous US-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Conventionally, US examination has been considered to have a limited capacity for the evaluation of the larynx. 10,11) However, laryngeal masses in well-selected patients can be assessed with US through suitable anatomical windows, such as the suprahyoid regions, thyrohyoid membrane, and cricothyroid membrane. 12,13) Moreover, the utility of US can be enhanced unless the patient's thyroid cartilage is completely ossified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventionally, US examination has been considered to have a limited capacity for the evaluation of the larynx. 10,11) However, laryngeal masses in well-selected patients can be assessed with US through suitable anatomical windows, such as the suprahyoid regions, thyrohyoid membrane, and cricothyroid membrane. 12,13) Moreover, the utility of US can be enhanced unless the patient's thyroid cartilage is completely ossified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported the feasibility and results of office-based US-CNB for laryngeal and hypopharyngeal masses. 10,12) This technique is feasible in selected patients with a suitable tumor location and allows deep biopsy under real-time US monitoring, leading to accurate pathological diagnosis. Therefore, US-CNB could be a good alternative to avoid general anesthesia only for diagnostic procedure, particularly in patients with severe comorbidities and a high risk for general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of ultrasound to image-guided biopsy of base of tongue, hypopharynx, thyroid nodules, and cervical lymph node metastases has been well documented, and its use in laryngeal cancer has been increasing in recent years. 1 - 4 Ultrasound-guided biopsy has high sensitivity and specificity, which are replicated through this technique to target laryngeal masses. 1 All patients in our study with squamous cell carcinoma were correctly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…While TCUS-guided FNA does not replace the role of DLB for tumor mapping and surgical preparation, it proved to be a low-risk alternative that allowed for rapid tissue diagnoses. 2 , 3 Many of these patients had significant airway abnormalities, which would have necessitated tracheostomy in 4 cases to safely perform DLB. Tracheostomy results in hospitalization, with relative delay in diagnosis and treatment as compared with TCUS-guided FNA, with potentially worse outcomes.…”
Section: Discussionmentioning
confidence: 99%